Forging an integrated Europe - Eichengreen, Barry J.; Frieden, Jeffry A. (Michigan studies in international political economy., 1998)
As European Integration has deepened and become more invasive the tension between the authority of the European Union and the autonomy of member states has increased. How fast and how far European integration will proceed are critical issues for scholars and policymakers in Europe and the United States. Barry Eichengreen and Jeffry Frieden have assembled a group of prominent economists and political scientists to discuss the most important - and most difficult - political and economic issues involved in European integration. The book focuses on three major issues: economic and monetary union, the reform and development of responsive political institutions for the Union, and the enlargement of the Union to include states to the east.